Pemberdayaan Kelompok Hadrah Kec. Penengahan dengan Pendekatan Multikultural: Penambahan Shalawat Berbahasa Prancis - Barnawi, Erizal; Safitri, Aulia Laila (Universitas Tanjungpura, 2024)
Hadrah groups in Penengahan District, South Lampung Regency have the potential to be empowered to improve their skills. This study aims to empower Hadrah groups through a multicultural approach by adding French-language shalawat. The research method used is qualitative through a participatory approach. Data was collected through observation, interviews, and documentation. The results of the study showed that: (1) Hadrah groups in Penengahan District, South Lampung Regency have the potential to be developed. They have the enthusiasm to learn and practice; (2) The multicultural approach by adding French-language shalawat can significantly improve the artistic quality of Hadrah and increase Hadrah participation in Penengahan District, South Lampung Regency; and (3) The community and Hadrah groups responded positively to the addition of French-language shalawat. Therefore, it can be stated that the empowerment of Hadrah groups in Penengahan District, South Lampung Regency through a multicultural approach by adding French-language shalawat has proven to be effective in improving the artistic quality of Hadrah and increasing the attractiveness and participation of Hadrah in Penengahan District, South Lampung Regency.